EDUKASI MASYARAKAT TENTANG PEMANFAATAN PUSKESMAS DALAM MENGOPTIMALKAN PELAYANAN KESEHATAN MASYARAKAT DI DESA GUNTING SAGA KEC. KUALUH SELATAN KAB. LABUHANBATU UTARA - Tarigan, Usaha Satria Pratama (Jurnal Pengabdian Masyarakat Putri Hijau, 2024)
Utilization of Community Health Centers can be interpreted as a concept that is applied to provide services over a long period of time and continuously to the community. As the most basic need. The aim of this Community Service Program is to provide community education regarding the use of community health centers in optimizing community health services in Gunting Saga Village, Kec. Kualuh Selatan District. North Labuhanbatu. Increasing public awareness by providing understanding to the public regarding the importance of utilizing community health center services to improve their health and welfare. Building Community Independence in Health by Encouraging the community to be more independent in maintaining their health, by utilizing community health center services as partners in maintaining health. This dedication reveals that health services have a very important role in maintaining people's health, especially during times of illness, where people's needs for health services will be met and health financing will be more secure with health insurance